2020
DOI: 10.3892/etm.2020.8945
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus seroprevalence in pregnant women in the western region of Romania: A large‑scale study

Abstract: Cytomegalovirus (CMV) infection is the most common congenital infection worldwide, and remains a significant cause of the neurological deficiency and sensory deafness in developed countries. Maternal primary infection, reactivation or reinfection during pregnancy may lead to fetal infection and congenital CMV syndrome. The purpose of this study was to analyze the CMV seroprevalence according to demographic features of pregnant women in western Romania as well as the evolution of CMV immunity in two time interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
42
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 19 publications
4
42
2
1
Order By: Relevance
“…This study is part of a larger project that demonstrated a decrease in the seroprevalence of Toxoplasma gondii , CMV and rubella virus, among women of reproductive age and pregnant women in western Romania over a decade from 2008 to 2018 [ 11 , 12 , 13 ]. Thus, our previous research showed a decrease in seroprevalence among women of reproductive age, between 2008–2010 and 2015–2018, from 43.8% to 38.8% [ 11 ], in the case of Toxoplasma gondii .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger project that demonstrated a decrease in the seroprevalence of Toxoplasma gondii , CMV and rubella virus, among women of reproductive age and pregnant women in western Romania over a decade from 2008 to 2018 [ 11 , 12 , 13 ]. Thus, our previous research showed a decrease in seroprevalence among women of reproductive age, between 2008–2010 and 2015–2018, from 43.8% to 38.8% [ 11 ], in the case of Toxoplasma gondii .…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ]. In the western region of Romania, our previous research showed also a decrease in CMV seroprevalence among women of reproductive age, from 94% to 91.8% [ 12 ]. An increased seroprevalence was found in women from rural compared to urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…This is the largest study on the seroprevalence of TORCH infections among women of reproductive age in Romania [ 11 , 12 ]. The presented results show that the rubella seronegative rate among women of reproductive age in the western region of Romania increased between 2008–2010 and 2015–2018 from 5.9% to 8.6%, above the European average of 7.6% [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review by Tanasa et al (1) entitled 'Anosmia and ageusia associated with coronavirus infection (COVID- 19)what is known?' summarizes the existing data regarding the association of anosmia and ageusia with the SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…In their study entitled 'Cytomegalovirus seroprevalence in pregnant women in the western region of Romania: A largescale study', Gorun et al (19) analyzed the CMV seroprevalence according to demographic features of pregnant women in western Romania, as well as the evolution of CMV immunity in two time intervals. The seroprevalence was higher in women from rural areas compared to those from urban areas.…”
mentioning
confidence: 99%